Cyclic Variations of Combustion Characteristics in Diesel Engine Operating With B20 Blends with Alcohol Additives - Mohd Hafizil, Mat Yasin; R., Mamat; Amir, Aziz; Ahmad Fitri, Yusop (2013)
Biodiesel is a renewable biological fuel which has higher density and viscosity as compared to mineral diesel. However, the simple approach to reduce the viscosity of biodiesel is to blend the mineral diesel with biodiesel. While the use of alcohol additives (ethanol and methanol) in the biodiesel blends fuel is to make lesser viscosity of the blend fuel. Different fuel properties produce different combustion characteristics of the blend fuels. Combustion studies on mineral diesel, B20 (biodiesel 20% + diesel 80%) and B20 blend fuels with alcohol additives (B20 E5 and B20 M5) were carried out using a Mitsubishi 4D68 multi-cylinder diesel engine. The combustion characteristics of an indirect injection diesel engine were examined by means of cyclic variation of peak cylinder pressure and mean indicated pressure (MIP). In-cylinder pressure was investigated for the various pressure crank angle history in this study. Statistical analysis of combustion characteristics for diesel engine have been carried out on three different engine loads; 20%, 40% and 60% at a constant engine speed of 2500 rpm using a combustion data of 200 cycles. The results show that at lower load, mineral diesel dominated the maximum peak cylinder pressure compared to other test fuels. However at higher load, B20, B20 E5 and B20 have surpassed mineral diesel for the maximum peak cylinder. It also remarked the variations of peak cylinder pressure of the test fuels influence most the mean indicated pressure (MIP) at three different engine loads.